ROLE OF TRIBALS IN THE REVOLUTION OF 1857 (WITH SPECIAL REFERENCE TO CHHATTISGARH) - Shukla, Pradeep (International Journal of Research -GRANTHAALAYAH, 2017)
As soon as the British rule established its foothold in India, it started inhuman atrocities, from which Chhattisgarh too was not untouched. Along with political atrocities, religious atrocities also started. Magleys, the chairman of the directors of the East India Company, said in the House of Commons in 1857, 'God has handed over this glorious kingdom of India to England so that the flag of victory of Jesus Christ starts flying from one end of India to the other.' In fact, sporadic incidents of discontent and rebellion in the Chhattisgarh region were seen even before 1857. From this point of view, in Chhattisgarh, a tribal region with the stigma of backwardness, national sentiments started taking birth indirectly in 1833. Devnath Singh, son of Jujhar Singh of Raigarh princely state, revolted against the British but did not succeed.